2008
DOI: 10.1177/0886260508314325
|View full text |Cite
|
Sign up to set email alerts
|

Premilitary Adult Sexual Assault Victimization and Perpetration in a Navy Recruit Sample

Abstract: Female ( n = 5,226) and male ( n = 5,969) U.S. Navy recruits completed a survey assessing their premilitary histories of adult sexual assault (SA), defined as attempted or completed rape since the age of 14. The survey was completed under anonymous or identified conditions. Overall, 39% of women reported premilitary SA victimization and 13% of men admitted premilitary SA perpetration. As predicted, rates were significantly higher in the anonymous than in the identified condition. For the sample of women as a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…Differences between community-residing women and female soldiers suggest that women who are drawn to military service may have more severe early life adversity, including sexual violence. Indeed, prior studies assessing sexual violence among women in the military have found estimates ranging from 28 to 50 %; estimates in the current study were consistent with some prior reports, 15,16 but lower than others. 17 The majority of sexual violence reported in this study occurred prior to the most recent deployment.…”
Section: Commentsupporting
confidence: 91%
See 2 more Smart Citations
“…Differences between community-residing women and female soldiers suggest that women who are drawn to military service may have more severe early life adversity, including sexual violence. Indeed, prior studies assessing sexual violence among women in the military have found estimates ranging from 28 to 50 %; estimates in the current study were consistent with some prior reports, 15,16 but lower than others. 17 The majority of sexual violence reported in this study occurred prior to the most recent deployment.…”
Section: Commentsupporting
confidence: 91%
“…12 Only three studies have assessed sexual violence prior to military engagement using non-treatment seeking active duty samples. [15][16][17] Among a representative sample of Air Force women, 28 % reported lifetime sexual violence. 15 In two studies using nonrepresentative samples of active duty soldiers, 38 % of female Navy recruits reported adolescent or adult sexual violence (since age 14), 16 and 6 % of Army men and 50 % of Army women reported lifetime sexual violence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining the cohesion of a military unit is prioritized above investigating or prosecuting reports of sexual harassment or assault, and an efficient veterans' health care system is prioritized over compassionate treatment of survivors of military sexual trauma (Campbell & Raja, 2005). While estimates of the rates of military sexual trauma tend to vary depending on the measurement (e.g., open-ended vs. specific) and population (e.g., active duty soldiers vs. treatment-seeking veterans), many sources tend to estimate that 20%-40% of women and 5%-10% of men in the military have experienced military sexual trauma (Stander, Merrill, Thomsen, Crouch, & Milner, 2008;Surìs & Lind, 2008). Yet legal and medical support is not easily gained for these individuals (Sadler et al, 2004), and prevention efforts have largely been unsuccessful (Campbell & Raja, 2005;Booth, Mengeling, Torner, & Sadler, 2011).…”
Section: Prioritiesmentioning
confidence: 99%
“…Among Asian American and Pacific Islander adolescents, high academic achievement has also been characterized as a protective factor against several forms of violence, such as throwing objects at others, robbery, "attacking someone with the intention of hurting or killing them" and involvement in "gang fights," (Wegner, Garcia-Santiago, Nishimura, & Hishinuma, 2010, p. 796). In a study examining female and male offenders, female violent offenders were found to have lower levels of education than male offenders, and were less likely to have prior employment (Rossegger et al, 2009 studies have shown that marriage may be a protective factor for certain types of violence in that married men were less likely to report engaging in sexual assaults than cohabitating men or men who reported "other" as their marital status (Stander, Merrill, Thomsen, Crouch, & Milner, 2008). In addition, in terms of general violence, those who reported being "never married" were more likely to engage in violent behaviour than married, divorced or separated men (Klassen & O'Connor, 1988).…”
Section: Contextual Factorsmentioning
confidence: 99%